ANALISIS PERSEPSI KERUMITAN, KEMUDAHAN, KEGUNAAN DAN KEPUASAN WAJIB PAJAK TERHADAP FASILITAS E-FILING SEBAGAI SARANA PENYAMPAIAN SPT MASA SECARA ONLINE DAN REALTIME (KAJIAN STUDI EMPIRIS: KOTA BATAM) - Nopiana, Puspita Rama; Yuliadi, Yuliadi (Aksara Public, 2017)
The purpose of this study is to analyze 1) perception of complexity, 2) perception of convenience, 3) perception of utility, 4) perception of service satisfaction 5) perception of complexity, ease, usefulness and satisfaction for taxpayers simultaneously to e-filing facilities as a means of delivery of SPT Online and Realtime Period in Batam City. Types of research and data collection methods that do with the survey method through questioner distributed to the respondent. The population in this study consists of taxpayers of individuals and entities residing in Batam City. The sample of this research is taxpayer in Batam City who reported SPT Masa through e-filing. The result of this research is 1) H1: shows that the perception of complexity does not have positive and significant relation for taxpayer to e-filing facility, 2) H2: shows that perception of ease does not have positive and significant relation for taxpayer to e-filing facility , 3) H3: shows that usability perception has positive and significant relation for taxpayer to e-filing facility, 4) H4: shows that perception of service satisfaction does not have positive and significant relation for taxpayer to e-filing facility 5) H5 : shows that the perception of complexity, ease, usefulness and satisfaction of service has a positive and significant simultaneous relationship for taxpayers to e-filing facility as a means of delivering online and realtime SPT in Batam City. Coefficient of determination equal to 50,9% and side 49,1% influenced by other factors